Keteladanan Orang Tua Berbasis Titus 2:1-10 Sebagai Upaya Mendidik Anak Dalam Keluarga - Tobing, Elisabeth Margaretha (NABISUK : Jurnal Teologi dan Pelayanan, 2024)
This research aims to determine the example of parents based on Titus 2:1-10 as en effort to educate children in the family. The research used qualitative fields methods in the form of interview were 6 people consisiting of: 2 men who were married, 2 women who were married, 2 teenage children. In depening the research, deep indicators were formed to build a grid of questions according to Exemplary in Titus 2:1-10. Through question variables, it is necessary to find out the extent of parental example in educating children in the congregation and teaching these variables as parents effort to educate children in the family. Based on the research result, it can be concluded that parent have not been able to become ideal role models as a basis for educating children. The role of parents in educating children is very important. Elders and Pastors must make serious efforts to implement effective methods, one of which is to teach the keys to achieving exemplary living by teaching sound Teachings as stated in Titus 2:1-10.